Influence of low-temperature annealing on the state of CdTe surface - Parfenyuk, O.A.; Ilashchuk, M.I.; Chupyra, S.M.; Burachek, V.R.; Korbutyak, D.V.; Krylyuk, S.G.; Vakhnyak, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Influence of low-temperature annealing on electrical and luminescent properties of semi-insulating n-CdTe:Sn is studied. It is shown that annealing at T ≥ 453 K modifies a near-surface layer of the crystals and this enhances the hole component of the conductivity. It is explained by Cd evaporation and subsequent enrichment of the near-surface layer with cadmium vacancies. Results of electrical measurements are confirmed by our low-temperature photoluminescence experiments.